Wstęp do Części I / Introduction to Part I - Puppel, Stanisław (Scripta Neophilologica Posnaniensia, 2019)
Part I of the current issue of Scripta Neophilologica Posnaniensia (Tom XVIII) has been entitled Imago mundi and contains a number of papers which were presented during an international conference entitled Image management: communicating through image, word and space. The subject matter of the Conference has generally focused on communication as a significant factor which participates in shaping the image of the individual communicators, institutions and social media, as well as on its effective management. The Conference took place at Adam Mickiewicz University on the 9th of June, 2017. It was organized jointly by the Department of Ecocommunication at AMU and Language, Culture and Politics Association (LCPA). Professor Aldona Sopata, Dean of the Faculty of Modern Languages and Literature, kindly opened the Conference.